Local Knowledge and Habits of Julung-julung Fishermen (Hemiramphus lutkei Valenciennes, 1847) in Buru Regency, Maluku - Evelin Tuhumuri; Matheos Talakua; Samsia Umasugi (Jurnal Penelitian Pendidikan IPA, 2026)
Julung-julung fishermen along the coast of Buru Regency, Maluku, have a structured organization and division of labor within their groups. The objective of this study is to describe the structure, functions, knowledge, and local customs of julung-julung fishing groups in Buru Regency. Data collection was conducted through observation and interviews with the fishermen (N=46). The results of the study indicate that julung-julung fishermen belong to the category of small-scale and traditional fishermen. Membership in the fishing groups is not restricted by age or educational level. The majority of group members work primarily as fishermen. Each julung-julung fishing group consists of a fishing boat owner (juragan) and crew members (masnait). There are no social status distinctions within the julung-julung fishing groups. The fishing boat owners and crew members work together in the julung-julung fishing operations according to their respective skills. Fishing is conducted based on knowledge passed down from their ancestors and has become a tradition practiced from generation to generation. They possess knowledge of water conditions, signs of the presence of julung-julung fish, fishing gear, fishing techniques, and the timing of fishing and landing the catch. The local knowledge and customs of these fishermen can be utilized to formulate policies for the sustainable management of julung-julung fisheries in Buru Regency.